2015
DOI: 10.1007/s00404-015-3738-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and perinatal outcomes in eclamptic women with posterior reversible encephalopathy syndrome

Abstract: This study indicates that PRES manifests predominantly with headache and visual impairment together. Adverse neonatal outcomes are also common in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
1
14
0
2
Order By: Relevance
“…15 Kurdgolu Z et al and Camara-Limarroy et al reported that infants of mothers with eclampsia complicated with PRES had low 1-minute APGAR score, these findings are similar to the present study. 40,41 Comparison of other studies with the present study parameter are shown in Table 4. Limitation of the present study is that, it is a retrospective study without any control group.…”
Section: Figure 2a 2b 2c and 2d: Mri Images Of One Of The Patients mentioning
confidence: 80%
“…15 Kurdgolu Z et al and Camara-Limarroy et al reported that infants of mothers with eclampsia complicated with PRES had low 1-minute APGAR score, these findings are similar to the present study. 40,41 Comparison of other studies with the present study parameter are shown in Table 4. Limitation of the present study is that, it is a retrospective study without any control group.…”
Section: Figure 2a 2b 2c and 2d: Mri Images Of One Of The Patients mentioning
confidence: 80%
“…Há relato de concomitância entre a ocorrência de cefaleia com alterações visuais em 60% das pacientes que apresentam PRES decorrente de eclâmpsia, o que traz um importante fato: maior ocorrência dos fenômenos visuais associados à PRES no período gravídico-puerperal (KURDOGLU Z, et al, 2015). Cozzolino M, et al (2015), sintetizam que independente da presença de cefaleia ou demais sinais e sintomas que ocorrem na PRES relacionado à gestação ou puerpério, raramente a PRES se desenvolverá na ausência de crises convulsivas.…”
Section: Resultados E Discusãounclassified
“…Studies have pointed out than 9 and the level of 24h serum uric acid in women with severe PE was significantly higher than the group without RPLS ( P= 0.012). 10 …”
Section: Discussionmentioning
confidence: 99%